2018
DOI: 10.24052/jbrmr/v13is01/art-18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of motivational factors on knowledge sharing behaviour of managers in Ready Made Garments (RMG) Industry of Bangladesh

Abstract: The study aimed to examine the impact of motivational factors on the knowledge sharing behaviour of managers in the Ready-Made Garments (RMG) industry of Bangladesh. Everyone has knowledge and can be part of knowledge sharing specially in organizations where employees need knowledge from the seniors or other personnel to perform better. However, barriers in the knowledge sharing process are common while some motivators could be effective to overcome those barriers and motivate individuals to share their knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 22 publications
3
26
1
1
Order By: Relevance
“…. (Razmerita, Kirchner & Nielsen, 2016) who found that employees like helping others was a factor that had relationship with knowledge sharing of the employees which is consistent with the findings of researchers (Islam, Jantan, Khan, Rahman & Monshi, 2018;Irma Susanty & Charles Wood, 2011) Self-Efficacy: For the employees to voluntarily share knowledge they must have the sense of selfefficacy that their experience and knowledge is valuable for the organization (Staplehurst & Ragsdell, 2010). In the model proposed by (Chau, 2018) self-efficacy and employee attitude were important factors for knowledge sharing.…”
Section: Knowledge Sharing Factors In Sme's and Large Organizationssupporting
confidence: 73%
“…. (Razmerita, Kirchner & Nielsen, 2016) who found that employees like helping others was a factor that had relationship with knowledge sharing of the employees which is consistent with the findings of researchers (Islam, Jantan, Khan, Rahman & Monshi, 2018;Irma Susanty & Charles Wood, 2011) Self-Efficacy: For the employees to voluntarily share knowledge they must have the sense of selfefficacy that their experience and knowledge is valuable for the organization (Staplehurst & Ragsdell, 2010). In the model proposed by (Chau, 2018) self-efficacy and employee attitude were important factors for knowledge sharing.…”
Section: Knowledge Sharing Factors In Sme's and Large Organizationssupporting
confidence: 73%
“…knowledge sharing is related to performance and evidenced that expenditure on collaborative R&D (research performed by team) has better contributions to performance (R. Du et al, 2007). This suggestion is somewhat concurrent with the notion of knowledge sharing and utilization of tacit knowledge requires high degrees of involvement of both knowledge holder and learner (Law and Chan, 2016;Islam, Jantan, Khan, Rahman, & Monshi, 2018). Moreover the suggestion agree with notion of knowledge creation is base for innovative activity .…”
Section: Performancementioning
confidence: 57%
“…However somewhat disagree with the finding of Mohamad and Ahmad (2012) found that positive significant relationship between information technology and KM practices in industrial company context and also Mazhar and Saeed (2018) found that positive and significant relationship between leadership commitment and organizational culture, and creativity. Further study evidenced that knowledge sharing has a non-linear insignificant relationship with performance which contradicts the conclusion of knowledge sharing impact on innovativeness are statistically significant positive effect (Islam, et al, 2018;Samir, 2020). This implies provision of knowledge sharing to the academic staffs couldn't assure positive contribution while performing KM practice in attainment of required performance.…”
Section: Organization and It Supportmentioning
confidence: 77%
“…Knowledge management is the process of creating, sharing, using, and managing the knowledge and information of an organisation (Liebowitz, 1999;Islam, Jantan, Khan, Rahman, & Monshi, 2018). Knowledge management efforts have a long history, including on-the-job discussions, formal apprenticeship, discussion forums, corporate libraries, professional training, and mentoring programs (Sanchez, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%